Knowledge of supplemental folic acid during pregnancy - Beatriz Barco Tavares; Ana Maria Neves Finochio Sabino; Juliana Cristina Lima; Claudia Tozzo Garcia (Universidad de Antioquia, 2015)
Objective.To identify the use of folic acid during pregnancy, as well as the new mothers´ knowledge about folic acid. Methodology. Quantitative, descriptive exploratory, and prospective study. A total of 198 mothers were interviewed in the pediatric outpatient service of Hospital de Base Sao José do Rio Preto, Brazil. They have taken their children for neonatal screening and formally consented to participating in the study. The research project was approved by the Research Ethics Committee (350,287). A specific instrument was used for data collection. The data were entered into an appropriate spreadsheet and later statistically analyzed. Pearson´s chi-squared test, p <0.15, was used. Results. On average, the interviewed mothers were 25 years old and received less than two minimum wages. Most had prenatal in the first quartile and a mean of seven appointments, starting the use of folic acid from the 7th to the 9th week of gestational age. However, when asked about the importance of folic acid and its action, almost the majority was not able to answer. Conclusion. Although daily acid supplementation is recommended in prenatal care, this study found that consumption is inadequate, contributing to the increased risk of fetal malformation. Healthcare professionals, especially nurses, should develop educational activities for women about the use of folic acid in the pre-gestation period and in the first pregnancy trimester.